The long‐term steady motion of Saturn's hexagon and the stability of its enclosed jet stream under seasonal changes. Issue 5 (7th March 2014) - Sánchez‐Lavega, A.; del, T.; Hueso, R.; Pérez‐Hoyos, S.; García‐Melendo, E.; Antuñano, A.; Mendikoa, I.; Rojas, J. F.; Lillo, J.; Barrado‐Navascués, D.; Gomez‐Forrellad, J. M.; Go, C.; et al.
Abstract We investigate the long‐term motion of Saturn's north pole hexagon and the structure of its associated eastward jet, using Cassini imaging science system and ground‐based images from 2008 to 2014. We show that both are persistent features that have survived the long polar night, the jet profile remaining essentially unchanged. During those years, the hexagon vertices showed a steady rotation period of 10 h 39 min 23.01 ± 0.01 s. The analysis of Voyager 1 and 2 (1980–1981) and Hubble Space Telescope and ground‐based (1990–1991) images shows a period shorter by 3.5 s due to the presence at the time of a large anticyclone. We interpret the hexagon as a manifestation of a vertically trapped Rossby wave on the polar jet and, because of their survival and unchanged properties under the strong seasonal variations in insolation, we propose that both hexagon and jet are deep‐rooted atmospheric features that could reveal the true rotation of the planet Saturn.